Age-related rarefaction in the fractal dimension of retinal vessel - Che Azemin, Mohd Zulfaezal; Kumar, Dinesh Kant; Wong, Tien Y.; Wang, Jie Jin; Mitchell, Paul; Kawasaki, Ryo; Wu, Henry (Elsevier Inc., 2012)
Previous work suggests a general reduction in complexity with aging, referred to as the aging-complexity theory. Fractal dimension (FD) of the vessels in the retina is a global measure of the complexity of the vasculature. However, earlier works did not find any correlation between aging and FD of the retinal vasculature, in contrast to the findings of reduced complexity in other parts of the body. The authors tested the hypothesis that reduced complexity develops with advancing age in the structure of the retinal vasculature. To overcome the limitations of earlier works, a three-dimensional representation of the vasculature, together with Fourier fractal dimension (FFD) techniques, was used. Based on the analysis of 748 retinal images taken of persons aged 49-89 years, we observed a significant decrease in the FFD with aging (p < 0.0001). These data provide evidence supporting rarefaction (i.e. reduction) of the retinal vasculature with aging, consistent with observations from other human organ systems.